Accumulation of Extracellular Hyaluronan by Hyaluronan Synthase 3 Promotes Tumor Growth and Modulates the Pancreatic Cancer Microenvironment. (24th July 2014) - Kultti, Anne; Zhao, Chunmei; Singha, Netai C.; Zimmerman, Susan; Osgood, Ryan J.; Symons, Rebecca; Jiang, Ping; Li, Xiaoming; Thompson, Curtis B.; Infante, Jeffrey R.; Jacobetz, Michael A.; Tuveson, David A.; et al.
Abstract : Extensive accumulation of the glycosaminoglycan hyaluronan is found in pancreatic cancer. The role of hyaluronan synthases 2 and 3 (HAS2, 3) was investigated in pancreatic cancer growth and the tumor microenvironment. Overexpression of HAS3 increased hyaluronan synthesis in BxPC-3 pancreatic cancer cells. In vivo, overexpression of HAS3 led to faster growing xenograft tumors with abundant extracellular hyaluronan accumulation. Treatment with pegylated human recombinant hyaluronidase (PEGPH20) removed extracellular hyaluronan and dramatically decreased the growth rate of BxPC-3 HAS3 tumors compared to parental tumors. PEGPH20 had a weaker effect on HAS2-overexpressing tumors which grew more slowly and contained both extracellular and intracellular hyaluronan. Accumulation of hyaluronan was associated with loss of plasma membrane E-cadherin and accumulation of cytoplasmic β -catenin, suggesting disruption of adherens junctions. PEGPH20 decreased the amount of nuclear hypoxia-related proteins and induced translocation of E-cadherin and β -catenin to the plasma membrane. Translocation of E-cadherin was also seen in tumors from a transgenic mouse model of pancreatic cancer and in a human non-small cell lung cancer sample from a patient treated with PEGPH20. In conclusion, hyaluronan accumulation by HAS3 favors pancreatic cancer growth, at least in part by decreasing epithelial cell adhesion, and PEGPH20 inhibits these changes and suppresses tumor growth.